PERANAN KEPOLISIAN DALAM PENCEGAHAN TINDAK PIDANA PEMBOBOLAN AUTOMATIC TELLER MACHINE DI WILAYAH HUKUM KEPOLISIAN RESOR KOTA PEKANBARU - JOSUA FEBRIANTO; Firdaus '; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Town of Pekanbaru with growth of urban which fast in such a way him become arsonistwanted where machine facility of Automatic Teller Machine spread over many and not allequiped facility of kemananan adequate. arsonist of theft with weight have ought to be arrestedand judged to remember this badness generate trouble service society. For that, role of Policevery required to utilize badness meminimalisir. Target of writing of this skripsi, first namely,execution of Role of Police in Prevention Of Doing An Injustice Leaked Automatic TellerMachine Territory Of Jurisdiction Police of Resor Town of Pekanbaru, both, executionresistance, and also third, strive to overcome resistance execution of Role of Police in PreventionOf Doing An Injustice Leaked Automatic Teller Machine Territory Of Jurisdiction Police ofResor Town of Pekanbaru.This Research type classified in research of sosiologis yuridis, because direct writerperform research accurate place or location. This research Police of Resor Town of Pekanbaru,while and population of sampel to represent the overall of related to problem of accurate in thisresearch, source of data the used primary data, data of sekunder data and of tertier, techniquedata collecting of research with observation, interview, bibliography study and enquette.From result of research of problem there fundamental three things able to be concludedis. First, Execution of Role of Police in Prevention Of Doing An Injustice Leaked AutomaticTeller Machine Territory Of Jurisdiction Police of Resor Town of Pekanbaru have been executedby maximizing effort of pre and emtif of preventif with aim to maximize function set of Police inPolice scope of Resor Town of Pekanbaru preventive early incidence badness society, but in theexecution still met a number of resistance. Both, Resistance Execution the limited amount ofpersonnel of field, existence of omission effort or ruining to evidence goods which by perpetratorof doing an injustice, the limited facilities and basic facilities and lack of kordinasi from each.Third, Effort overcome resistance execution of Role of Police in Prevention Of Doing AnInjustice Leaked Automatic Teller Machine Territory Of Jurisdiction Police of Resor Town ofPekanbaru in the form of make-up of Personnel quality and amount proposing of request ofaddition of personnel to Polda Riau, to be placed to to undertake Police of Resor Town ofPekanbaru, construction bounce, with stages;steps like construction of mental attitude andpersonnel discipline in the form of spiritial siraman personnel can improve godfearing to GodWhich Single The most, as according to each trust and religion, construction bounce to increaseand always play fair, devoted of duty, and comprehend its responsibility will and also everrespect others rights, and deed of moral based on to importance of society.